Behavioural and electrophysiological modulations induced by transcranial direct current stimulation in healthy elderly and Alzheimer's disease patients: A pilot study. Issue 11 (November 2019) - Cespón, J.; Rodella, C.; Miniussi, C.; Pellicciari, M.C.
Highlights: Transcranial direct current stimulation (tDCS) modulated neural activity in healthy elderly and Alzheimer's disease patients. Neural modulations may depend on the interaction between tDCS polarity and neural state. Neural modulations induced by tDCS were related to working memory improvements. Abstract: Objective: To investigate whether anodal and cathodal transcranial direct current stimulation (tDCS) can modify cognitive performance and neural activity in healthy elderly and Alzheimer's disease (AD) patients. Methods: Fourteen healthy elderly and twelve AD patients performed a working memory task during an electroencephalogram recording before and after receiving anodal, cathodal, and sham tDCS over the left dorsolateral prefrontal cortex. Behavioural performance, event-related potentials (P200, P300) and evoked cortical oscillations were studied as correlates of working memory. Results: Anodal tDCS increased P200 and P300 amplitudes in healthy elderly. Cathodal tDCS increased P200 amplitude and frontal theta activity between 150 and 300 ms in AD patients. Improved working memory after anodal tDCS correlated with increased P300 in healthy elderly. In AD patients, slight tendencies between enhanced working memory and increased P200 after cathodal tDCS were observed. Conclusions: Functional neural modulations were promoted by anodal tDCS in healthy elderly and by cathodal tDCS in AD patients. Significance: Interaction between tDCS polarity and the neural state (e.g., hyper-excitability exhibited by AD patients) suggests that appropriate tDCS parameters (in terms of tDCS polarity) to induce behavioural improvements should be chosen based on the participant's characteristics. Future studies using higher sample sizes should confirm and extend the present findings.